Antimicrobial and molecular resistance profiles of bacterial isolates from poultry production environment - Fernandes, Marina Mota; Silva, Endria Virgínia Alves; Reis, Beatriz Barbosa; Marques, Gessyk Monteiro; Deusdará, Tullio Teixeira; Brito, Hélio de Sousa; Ferreira, Marcela Oliveira; Silva, Keytte Fernanda Vieira; Baptista, Ana Angelita Sampaio; Nascimento, Vladimir Pinheiro do; et al. (Revista de Ciencias Agrícolas, 2024)
Poultry farming is a relevant industry in Brazil, providing essential animal protein. However, such commercial activity faces significant challenges from bacterial-based diseases, which can impact both animal health and quality product. In this context, this study aimed to identify bacterial strains and evaluate their antimicrobial resistance profiles in poultry farms in southern Tocantins, Brazil. Samples were collected from different stages of poultry production, and the antimicrobial susceptibilities were assessed through antibiogram tests, where bacterial isolates were exposed to 17 antibiotics commonly used in bacterial infection treatment. Bacterial isolates were identified by 16S rRNA gene sequencing, and phylogenetic analysis was used to group them based on genetic similarities. Five isolates were identified: Glutamicibacter creatinolyticus (IGA1), Enterococcus gallinarum (IGA2), Enterobacter mori (IGA3), Lysinibacillus fusiformis (IGA4), and Enterococcus faecalis (IGA5). Antibiotic susceptibility tests revealed significant variations in resistance profiles, with some isolates exhibiting multidrug-resistant (MDR) phenotypes. IGA1 was classified as multidrug-resistant, showing resistance to imipenem, meropenem, ceftazidime, trimethoprim, and doxycycline. IGA2 exhibited resistance to β-lactam antibiotics, including ceftazidime, cefepime, doxycycline, imipenem, meropenem, piperacillin-tazobactam, and tetracycline. IGA3 was resistant to aztreonam and trimethoprim, while IGA4 showed resistance to ceftazidime and cefepime but sensitivity to ciprofloxacin and linezolid. IGA5 did not show resistance to any of the tested antimicrobials. Collectively, our findings highlight bacterial diversity and antibiotic resistance in poultry fams, reinforcing the need for continuous monitoring and effective antimicrobial control strategies to promote animal health, ensure food safety, and prevent the transmission of multidrug-resistant bacteria to humans.